The use of the clarinets and bass clarinets in combination with other instruments to potray the libretto of Puccini's opera Tosca - Van der Mescht, Heinrich Hermann (University of Pretoria, 2013)
Dissertation (M Mus (Performing Art))--University of Pretoria, 2007.